MATERIALISM AND IMPULSIVE BUYING: EVIDENCE OF BUY-NOW-PAY-LATER AS A MEDIATOR AMONG INDONESIAN CONSUMERS - Rizki , Kurniady; Pradana, Mahir; Kartawinata, Budi Rustandi (PT. Jurnal Center Indonesia Publisher, 2025)
The rapid diffusion of Buy-Now-Pay-Later (BNPL) services has reshaped consumption in emerging economies. This article examines how materialistic value orientations stimulate impulsive buying through BNPL usage among Indonesian PayLater users. A cross-sectional survey of 670 respondents was analysed with partial least-squares structural-equation modelling (PLS-SEM). Materialism had a strong positive effect on BNPL adoption (β = 0.762) and a moderate direct effect on impulsive buying (β = 0.350). BNPL, in turn, exerted a substantial impact on impulsive buying (β = 0.480) and partially mediated the materialism–impulsivity link (indirect β = 0.366). The model explained 65% of BNPL variance and 72% of impulsive buying variance, while exhibiting acceptable fit indices (SRMR = 0.035; NFI = 0.885). Findings highlight BNPL’s dual role as a financial innovation and a behavioural catalyst, raising implications for platform design, consumer literacy programmes, and regulatory oversight.